2015
DOI: 10.1002/jobm.201500364
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time PCR based analysis of metal resistance genes in metal resistant Pseudomonas aeruginosa strain J007

Abstract: A uranium (U)-resistant and -accumulating Pseudomonas aeruginosa strain was characterized to assess the response of toxic metals toward its growth and expression of metal resistance determinants. The bacterium showed MIC (minimum inhibitory concentration) values of 6, 3, and 2 mM for Zn, Cu, and Cd, respectively; with resistance phenotype conferred by periplasmic Cu sequestering copA and RND type heavy metal efflux czcA genes. Real-time PCR-based expression analysis revealed significant upregulation of both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…4). Choudhary and Sar (2016) have presented similar results which found significant upregulation of czcA gene in P. aeruginosa strain upon exposure only to low concentrations of zinc and cadmium for short duration of their influences on bacterium. Similarly, Abdelatey et al (2011) have also confirmed the nccA-like gene inductions by addition of low cobalt and cadmium concentrations to the medium in Pseudomonas sp.…”
Section: Expression Of Czca-nm15i Resistance Genesupporting
confidence: 62%
“…4). Choudhary and Sar (2016) have presented similar results which found significant upregulation of czcA gene in P. aeruginosa strain upon exposure only to low concentrations of zinc and cadmium for short duration of their influences on bacterium. Similarly, Abdelatey et al (2011) have also confirmed the nccA-like gene inductions by addition of low cobalt and cadmium concentrations to the medium in Pseudomonas sp.…”
Section: Expression Of Czca-nm15i Resistance Genesupporting
confidence: 62%
“…The RND superfamily of efflux proteins was first described as a related group of membrane transport proteins involved in heavy metal resistance ( Ralstonia metallidurans ), nodulation ( Mesorhizobium loti ) and cell division ( E. coli ). These toxic elements are often present in their habitat hence the need for an efflux system (Rademacher and Masepohl 2012 ; Choudhary and Sar 2016 ). The RND pump proteins have one member that has a surprising substrate—unfolded polypeptides.…”
Section: Endogenous Functions Of Efflux Transportersmentioning
confidence: 99%
“…Upregulation of these genes did not seem to correlate with the heavy metal concentrations since majority of the heavy metal concentrations decreased after treatment ( Figure 6 and Table S6). However, earlier studies have reported a lack of correlation between the concentration of heavy metals and related resistance genes, suggesting that acute exposure of sub-lethal concentrations of these compounds were sufficient to trigger the expression of resistance genes [59,60]. Alternatively, the upregulation of these efflux pumps may be co-selected for by chlorination so as to regulate the concentration gradient of ROS generated in the chlorination chamber [61,62] and intracellularly [17].…”
Section: Discussionmentioning
confidence: 99%
“…The metal content ( 24 Mg, 27 Al, 47 Ti, 53 Cr, 55 Mn, 56 Fe, 57 Fe, 59 Co, 60 Ni, 63 Cu, 66 Zn, 90 Zr, 107 Ag, 111 Cd, 202 Hg, and 208 Pb) of October 2017 wastewater samples were measured on an inductively coupled plasma mass spectrometry (ICP-MS) (Agilent 7500). Wastewater samples were filtered through 0.22 µm Whatman™ Puradisc 23-mm syringe filters (GE Healthcare, Little Chalfort, Buckinhamshire, UK) prior to measurement.…”
Section: Icp-msmentioning
confidence: 99%